2008
DOI: 10.1007/s10827-008-0128-0
|View full text |Cite
|
Sign up to set email alerts
|

Stability and structural constraints of random brain networks with excitatory and inhibitory neural populations

Abstract: The stability of brain networks with randomly connected excitatory and inhibitory neural populations is investigated using a simplified physiological model of brain electrical activity. Neural populations are randomly assigned to be excitatory or inhibitory and the stability of a brain network is determined by the spectrum of the network's matrix of connection strengths. The probability that a network is stable is determined from its spectral density which is numerically determined and is approximated by a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
(99 reference statements)
1
23
0
Order By: Relevance
“…Functional patterns on hierarchically modular architectures have specifically been shown to display computationally advantageous dynamics characterized by stability and diversity [33], unlike simulated dynamics on either random or non-hierarchically small-world architectures [34]. Sporns provides a simple generative model for fractal hierarchical networks and shows further relationships between their structural and functional properties, suggesting that connectivity may strongly constrain dynamics [32], [35]. Computational models of hierarchical modularity have shown that networks configured in this way have the distinctive advantage of being robustly stable under large scale reconnection of substructure [36].…”
Section: Discussionmentioning
confidence: 99%
“…Functional patterns on hierarchically modular architectures have specifically been shown to display computationally advantageous dynamics characterized by stability and diversity [33], unlike simulated dynamics on either random or non-hierarchically small-world architectures [34]. Sporns provides a simple generative model for fractal hierarchical networks and shows further relationships between their structural and functional properties, suggesting that connectivity may strongly constrain dynamics [32], [35]. Computational models of hierarchical modularity have shown that networks configured in this way have the distinctive advantage of being robustly stable under large scale reconnection of substructure [36].…”
Section: Discussionmentioning
confidence: 99%
“…To apply this continuum model to brain networks we previously used a number of simplifying assumptions. In particular, we assumed that all neural populations have instantaneous dendritic response times and there is no time delay for a signal to be sent from one population to the other (Gray and Robinson, 2006, 2008, 2009b,a; Robinson et al, 2009). For this study we relax some of these assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…The specific random networks we investigate are the same random networks we have previously investigated (Gray and Robinson, 2006, 2008, 2009a,b). These networks consist of excitatory and inhibitory connections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In (14) the quantity N a from (1) is only nonzero in the case of N s and has been written as an integral over an input from the n population activity Q n , which is included in the sum over b. If the sum over b were restricted to exclude the n population, an equivalent additional term N s would appear instead on the right of (14) for a = s, with [26,56] N s (r,t) = G sn L(ω)φ sn (r,t),…”
Section: Neural Field Theorymentioning
confidence: 99%